Binder for solid-state battery and solid-state battery

A norbornene-based binder with ethylene oxide structure addresses the adhesion issues in solid-state batteries, ensuring stable electrode attachment and enhanced conductivity, thereby improving battery performance and manufacturing efficiency.

JP2025007469APending Publication Date: 2025-01-17SUMITOMO BAKELITE CO LTD

Patent Information

Application Number
JP2023108897
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Conventional binders for solid-state batteries exhibit insufficient adhesion between electrode active materials and current collectors, leading to issues such as electrode detachment during manufacturing and reduced battery capacity due to expansion and contraction during charging and discharging.

Method used

A binder for solid-state batteries is developed with a norbornene-derived structure in the main chain and an ethylene oxide structure in the side chain, providing excellent adhesion and ionic conductivity, allowing for stable bonding of electrode active materials to current collectors without high-temperature treatment.

Benefits of technology

The binder ensures stable adhesion of electrode active materials to current collectors, preventing detachment and maintaining excellent charging/discharging characteristics, even under conditions of expansion and contraction, while also offering improved ionic conductivity and solubility in a wide range of solvents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025007469000001_ABST
    Figure 2025007469000001_ABST
Patent Text Reader

Abstract

To provide a binder for a solid-state battery having excellent adhesion to an electrode active material and a current collector, and to provide a solid-state battery containing the binder for a solid-state battery.SOLUTION: A binder for a solid-state battery according to the present invention includes a resin component having a norbornene-derived structure in the main chain and an ethylene oxide structure in the side chain. The resin component preferably contains a monomer component represented by the following formula (NB) (In the formula, R1 is a hydrogen atom or a hydrocarbon group, R2, R3, and R4 are each independently a hydrogen atom or an organic group having 1 to 3 carbon atoms, n is an integer of 1 or more, and a1 is 0, 1, or 2.)SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a binder for a solid-state battery and a solid-state battery. [Background technology]

[0002] A battery contains a positive electrode active material and a negative electrode active material as electrode active materials. In the case of lithium ion batteries, for example, various lithium-containing metal oxides such as lithium iron phosphate, lithium cobalt oxide, lithium nickel oxide, lithium manganate, and spinel-based lithium compounds are used as the positive electrode active material, and silicon-based active materials such as Si, Si alloys, and silicon oxide, carbon-based active materials such as graphite and hard carbon, various oxide-based active materials such as lithium titanate, metallic lithium, lithium alloys, and the like are used as the negative electrode active material.

[0003] The electrode active material is fixed to the current collector by a binder. In addition to fixing the electrode to the current collector, the binder is required to fulfill many other roles, including: (1) aiding in dispersion and maintaining the dispersed quality when the electrode active material is mixed, (2) ensuring viscosity when the electrode active material is applied and controlling the thickness of the electrode layer immediately after application, (3) binding the electrode active material and bonding it to the current collector, (4) assisting the sliding of electrode active material particles when the electrode is pressed and maintaining them at their destination, (5) providing ionic and electrical conductivity, and other functions such as not reacting with the electrolyte as a side effect and being stable to the potential applied to the area of ​​use.

[0004] In such battery electrodes, PVDF (polyvinylidene fluoride) has conventionally been widely used as a binder for electrode active materials (see, for example, Patent Document 1).

[0005] However, conventional binders have insufficient adhesion to the electrode active material and the current collector, and the binder cannot fix a sufficient amount of the electrode active material to the current collector, which causes problems such as failure to obtain a battery with a sufficiently large initial capacity. In addition, for example, during the process of cutting the electrode to a specific size during battery production, or in the case of a secondary battery, expansion and contraction of the electrode occurs during repeated charging and discharging, which leads to the electrode active material falling off the current collector. This causes problems such as a decrease in battery capacity and failure to provide sufficiently excellent charge and discharge characteristics in the case of a secondary battery. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent No. 7044673 Summary of the Invention [Problem to be solved by the invention]

[0007] An object of the present invention is to provide a binder for a solid battery having excellent adhesion to an electrode active material and a current collector, and to provide a solid battery containing the binder for a solid battery. [Means for solving the problem]

[0008] These objects can be achieved by the present invention described below in (1) to (10). (1) A binder for a solid-state battery, comprising a resin component having a norbornene-derived structure in its main chain and an ethylene oxide structure in its side chain.

[0009] (2) The binder for a solid battery according to the above (1), wherein the resin component contains a monomer component represented by the following formula (NB):

[0010] [ka] (In formula (NB), R 1is a hydrogen atom or a hydrocarbon group, and R 2 , R 3 and R 4 are each independently a hydrogen atom or an organic group having 1 to 3 carbon atoms, n is an integer of 1 or more, and a1 is 0, 1, or 2.

[0011] (3) The binder for a solid state battery according to the above (2), wherein n in the above formula (NB) is an integer of 2 or more and 6 or less.

[0012] (4) The binder for a solid battery according to the above (2) or (3), wherein the monomer component is represented by the following formula [I]:

[0013] [ka] (In formula [I], n is an integer of 1 or more, and R is a hydrogen atom or a hydrocarbon group.)

[0014] (5) The binder for a solid battery according to any one of (1) to (4) above, wherein the weight average molecular weight of the resin component is 10,000 or more and 400,000 or less.

[0015] (6) The binder for a solid battery according to any one of (1) to (5) above, wherein the average degree of polymerization of the resin component is 25 or more and 1,800 or less.

[0016] (7) The binder for a solid battery according to any one of (1) to (6), wherein the softening point of the resin component is 25° C. or higher and 120° C. or lower.

[0017] (8) The binder for a solid battery according to any one of (1) to (7) above, which bonds an electrode active material contained in a positive electrode layer to a current collector.

[0018] (9) The binder for a solid battery according to any one of (1) to (7), which bonds an electrode active material contained in a negative electrode layer to a current collector.

[0019] (10) a positive electrode layer; A negative electrode layer; an electrolyte layer located between the positive electrode layer and the negative electrode layer; A solid-state battery comprising: A solid-state battery comprising the binder for solid-state batteries according to any one of (1) to (7) above. Effect of the Invention

[0020] According to the present invention, it is possible to provide a binder for a solid battery having excellent adhesion to an electrode active material and a current collector, and to provide a solid battery containing the binder for a solid battery. [Brief description of the drawings]

[0021] [Figure 1] FIG. 1 is a vertical cross-sectional view illustrating an example of a solid-state battery. [Diagram 2] 1A to 1C are diagrams illustrating a method for producing a test sample. [Diagram 3] 1 is a photograph illustrating a method for a peel test. [Figure 4] 1 shows stress-strain curves for binders for solid state batteries in Examples 1 and 3. [Diagram 5] 1 is a stress-strain curve for a binder for a solid battery of Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] The present invention will now be described in detail with reference to the accompanying drawings. [1] Binders for solid-state batteries The binder for a solid battery of the present invention is a binder used in a solid battery.

[0023] In the present invention, a solid-state battery is a battery that includes a solid electrolyte. The solid electrolyte is a concept that includes all-solid electrolytes, semi-solid electrolytes, and gel electrolytes, and may contain a liquid component or an electrolytic solution in addition to a material for a solid electrolyte.

[0024] The binder for a solid battery of the present invention bonds, for example, an electrode active material contained in an electrode layer to a current collector in a solid battery.

[0025] In the following description, a representative example will be described in which the binder for a solid battery of the present invention bonds an electrode active material contained in an electrode layer to a current collector in a solid battery.

[0026] The binder for a solid-state battery of the present invention is characterized by containing a resin component having a norbornene-derived structure in the main chain and an ethylene oxide structure in the side chain.

[0027] This makes it possible to provide a binder for a solid battery that has excellent adhesion to an electrode active material and a current collector.

[0028] As a result, by using the binder for a solid battery of the present invention, the electrode active material and the current collector can be suitably bonded together, and a sufficient amount of the electrode active material can be fixed to the current collector.

[0029] This makes it possible to prevent the electrode active material from falling off the current collector, for example, even in a process in which the electrode is cut to a specific size during battery production, or in the case of a secondary battery, when the electrode expands and contracts during repeated charging and discharging, thereby preventing a decrease in battery capacity and making the charge and discharge characteristics of the secondary battery sufficiently excellent.

[0030] Such excellent effects are believed to be obtained for the following reasons: By including a resin component having a norbornene-derived structure in the main chain, crystallization that is likely to occur with an ethylene oxide structure alone can be suppressed, and excellent adhesion to electrode active materials, current collectors, etc. can be stably maintained.

[0031] This allows the electrode active material and the current collector to be stably and suitably joined, and prevents the electrode active material from falling off the current collector more reliably.

[0032] Furthermore, by including a resin component having a rigid norbornene-derived structure in the main chain, good mechanical properties can be obtained when the resin is molded into a film or the like.

[0033] Furthermore, since the binder for a solid battery of the present invention contains a resin component having a norbornene-derived structure in its main chain, excellent ion conductivity can be maintained even in a relatively low temperature range.

[0034] Generally, if an oxide-based inorganic solid electrolyte is not subjected to high-temperature treatment such as sintering, the interface resistance between the electrolyte and the electrode material increases, causing problems in charging and discharging, but by using the binder for solid batteries of the present invention, the electrolyte can be suitably bonded to the electrode without high-temperature treatment such as sintering, and good charging and discharging characteristics can be obtained. As described above, the charging and discharging characteristics, reliability, etc. of a battery made of a material containing the binder for solid batteries can be excellent.

[0035] [1-1] Resin component As described above, the binder for a solid battery of the present invention contains a resin component having a norbornene-derived structure in the main chain and an ethylene oxide structure in the side chain.

[0036] An example of the norbornene-derived structure is the structure represented by the following formula [II] as a monomer.

[0037] [ka] (At least one of R1, R2, R3, R4, R5, R6, R7, R8, R9, and R10 in formula [II] is a single bond (direct bond) or a divalent atom or atomic group bonded to the side chain, and the rest are monovalent atoms or atomic groups.)

[0038] The divalent atomic group may, for example, be a linear or branched alkylene group. The monovalent atom includes, for example, a hydrogen atom.

[0039] Examples of the monovalent atomic group include hydrocarbon groups such as alkyl groups, alkenyl groups, and alkynyl groups, and further include structures in which these are bonded to the divalent atom or divalent atomic group.

[0040] In particular, in the norbornene-derived structure, only one of R1 to R10 in the above formula [II] is a single bond bonded to the side chain, and the remaining nine are preferably hydrogen atoms.

[0041] This makes it possible to more significantly exhibit the effects of the present invention as described above. In addition, the synthesis of the monomers that are the raw materials of the resin component can be carried out in a higher yield, and the polymerization reaction of the monomers can also proceed more efficiently, thereby increasing the yield of the resin component.

[0042] In this case, the single bond bonded to the side chain is preferably any one of R3 to R6 in the above formula [II].

[0043] This allows the effects of the present invention to be more pronounced as described above, and also allows the synthesis of the monomers that are the raw materials of the resin component to be carried out in a higher yield, and allows the polymerization reaction of the monomers to proceed more efficiently, thereby further increasing the yield of the resin component.

[0044] When the resin component contains a structure represented by the above formula [II] as a norbornene-derived structure, the resin component may contain, within the molecule, a plurality of different structures among the structures represented by the above formula [II].

[0045] The resin component has an ethylene oxide structure in the side chain. The ethylene oxide structure may be one that exists alone (one that does not have a structure in which ethylene glycol molecules are condensed with each other) or one that has a repeating structure (one that has a structure in which ethylene glycol molecules are condensed with each other), but one that has a repeating structure (one that has a structure in which ethylene glycol molecules are condensed with each other) is preferable.

[0046] This makes it possible to improve the adhesion of the binder for a solid battery to the electrode active material, the current collector, etc., and the ion conductivity.

[0047] In particular, the resin component preferably contains a monomer component represented by the following formula (NB):

[0048] [ka] (In formula (NB), R 1 is a hydrogen atom or a hydrocarbon group, and R 2 , R 3 and R 4 are each independently a hydrogen atom or an organic group having 1 to 3 carbon atoms, n is an integer of 1 or more, and a1 is 0, 1, or 2.

[0049] This allows the effects of the present invention to be more pronounced, as described above, and also improves the stability and ease of handling of the sheet when processed into a sheet material, as described below.

[0050] R in the above formula (NB) 1 may be a hydrogen atom or a hydrocarbon group, but is preferably an alkyl group having 1 to 4 carbon atoms, and more preferably a methyl group.

[0051] This allows the effects of the present invention to be more pronounced, as described above, and also improves the stability and ease of handling of the sheet when processed into a sheet material, as described below.

[0052] R in the above formula (NB)2 , R 3 and R 4 may each independently be a hydrogen atom or an organic group having 1 to 3 carbon atoms, and is preferably a hydrogen atom.

[0053] This allows the effects of the present invention to be more pronounced as described above, and also improves the stability and ease of handling of the sheet when processed into a sheet material as described below.

[0054] When the ethylene oxide structure constituting the side chain of the resin component has a repeating structure (having a structure in which ethylene glycol molecules are condensed together), the number of ethylene glycol molecules in the ethylene oxide structure is preferably 2 to 6, more preferably 2 to 5, and even more preferably 2 to 3. More specifically, for example, when the resin component contains a monomer component represented by the above formula (NB), n in the above formula (NB) may be an integer of 1 or more, but is preferably an integer of 2 to 6, more preferably an integer of 2 to 5, and even more preferably 2 or 3.

[0055] This allows the effects of the present invention to be more pronounced as described above, and also improves the stability and ease of handling of the sheet when processed into a sheet material as described below.

[0056] The resin component may contain, in a molecule, a plurality of types of structures having different numbers of condensation of ethylene glycol molecules.

[0057] As described above, the resin component preferably contains a monomer component represented by the above formula (NB). Among the monomer components represented by the above formula (NB), it is preferable that the resin component contains a monomer component represented by the following formula [I]:

[0058] [ka] (In formula [I], n is an integer of 1 or more, and R is a hydrogen atom or a hydrocarbon group.)

[0059] This allows the above-mentioned effects of the present invention to be more significantly exhibited, and also allows the ion conductivity of the binder for solid state batteries to be made higher, and also allows the stability and handling of the sheet to be improved when processed into a sheet material as described below.

[0060] When the resin component contains a monomer component represented by the above formula (NB), the resin component may contain multiple different types of monomer components represented by the above formula (NB) in the molecule.

[0061] The resin component may have a norbornene-derived structure in the main chain, and may have a structure not derived from norbornene (e.g., a monomer component other than the above formula [II]) in addition to the norbornene-derived structure in the main chain.

[0062] The proportion of monomer components having a structure derived from norbornene in all monomer components constituting the main chain of the resin component is preferably 95.0 mol % or more, more preferably 98.0 mol % or more, and even more preferably 100 mol %.

[0063] The resin component only needs to have an ethylene oxide structure in the side chain, and may have a structure other than the ethylene oxide structure in addition to the ethylene oxide structure in the side chain.

[0064] The proportion of the monomer component represented by the above formula [I] in all the monomer components constituting the resin component is preferably 90.0 mol % or more, more preferably 95.0 mol % or more, and even more preferably 100 mol %.

[0065] The weight average molecular weight of the resin component is preferably 10,000 or more and 400,000 or less, more preferably 30,000 or more and 350,000 or less, and even more preferably 50,000 or more and 300,000 or less.

[0066] This makes it possible to achieve a higher level of adhesion of the solid battery binder to the electrode active material, current collector, etc., as well as the stability and handleability of the sheet when processed into a sheet material as described below.

[0067] The average degree of polymerization of the resin component is preferably 25 or more and 1,800 or less, more preferably 75 or more and 1,500 or less, and even more preferably 100 or more and 1,000 or less.

[0068] This makes it possible to achieve a higher level of adhesion of the solid battery binder to the electrode active material, current collector, etc., as well as the stability and handleability of the sheet when processed into a sheet material as described below.

[0069] The softening point of the resin component is preferably 25°C or higher and 140°C or lower, more preferably 50°C or higher and 130°C or lower, and even more preferably 75°C or higher and 120°C or lower.

[0070] This makes it possible to achieve a higher level of adhesion of the solid battery binder to the electrode active material, current collector, etc., as well as the stability and handleability of the sheet when processed into a sheet material as described below.

[0071] The softening point can be determined using TMA / SS6100 under the conditions of a temperature rise rate of 3° C. / min and a compression load of 30 mN. In the examples described later, the softening point was determined under such conditions.

[0072] The content of the resin component in the binder for a solid battery of the present invention is preferably 80.0% by mass or more, more preferably 90.0% by mass or more, and even more preferably 95.0% by mass or more.

[0073] This allows the effects of the present invention to be more pronounced as described above, and also improves the stability and ease of handling of the sheet when processed into a sheet material as described below.

[0074] Meanwhile, PVDF (polyvinylidene fluoride), which has been widely used as a binder for conventional batteries, is soluble only in relatively highly polar solvents such as N-methyl-2-pyrrolidone (NMP) and acetone.

[0075] Therefore, when manufacturing batteries using PVDF as a binder, a "good" solvent with appropriate dissolving power for PVDF is selected, and the mixture is stirred, with heating if necessary, to prepare a homogeneous solution. However, PVDF powder has a tendency to agglomerate during stirring, so it takes a long time for the solvent to penetrate the agglomerates and completely dissolve the powder to obtain a homogeneous solution.

[0076] This tendency is stronger for PVDF with a high molecular weight, which takes a longer time to dissolve in an organic solvent such as NMP or acetone, thereby reducing productivity.

[0077] Furthermore, highly polar solvents may cause side reactions with inorganic solid electrolytes such as oxides and sulfides, and the reality is that the use of highly polar solvents should be avoided as much as possible.

[0078] In contrast, in the binder for solid batteries of the present invention, the resin component has high solubility in a wide variety of solvents, including solvents with relatively low polarity. In other words, by manufacturing a battery using the binder for solid batteries of the present invention, the selection of solvents to be used can be expanded and productivity can be improved. In addition, it can be said that the possibility of side reactions with the inorganic solid electrolyte as described above is low.

[0079] The binder for solid-state batteries of the present invention contains the resin component (a resin component having a norbornene-derived structure in the main chain and an ethylene oxide structure in the side chain), but may further contain other resin components. Hereinafter, such resin components are also referred to as "other resin components."

[0080] Examples of the other resin components include a resin material having a norbornene-derived structure in the main chain but not having an ethylene oxide structure in the side chain, and a resin material having an ethylene oxide structure in the side chain but not having a norbornene-derived structure in the main chain.

[0081] Other resin components include, for example, PVDF, PTFE (polytetrafluoroethylene), styrene-butadiene copolymer, polyimide, polyamide, polyvinyl alcohol, polyvinyl butyral, and derivatives thereof.

[0082] However, the ratio of other resin components in the binder for solid state batteries of the present invention is preferably 50.0 mass % or less, more preferably 40.0 mass % or less, and even more preferably 30.0 mass % or less.

[0083] [2]Battery Next, the battery of the present invention will be described.

[0084] The battery of the present invention is a battery including a positive electrode layer, a negative electrode layer, an electrolyte layer located between the positive electrode layer and the negative electrode layer, and a current collector, and is characterized in that it contains the above-mentioned binder for solid state batteries of the present invention.

[0085] This makes it possible to provide a battery containing a binder for a solid battery that has excellent adhesion to an electrode active material and a current collector.

[0086] As a result, the electrode active material and the current collector can be suitably joined, a sufficient amount of the electrode active material can be fixed to the current collector, and the electrode active material can be prevented from falling off the current collector, resulting in excellent charge / discharge characteristics, reliability, etc. of the battery.

[0087] Hereinafter, among batteries, a solid-state battery as a secondary battery will be described as a representative example. FIG. 1 is a vertical cross-sectional view illustrating an example of a solid-state battery.

[0088] As shown in FIG. 1, a solid-state battery 10 includes a positive electrode layer 11 which is one electrode layer, a negative electrode layer 12 which is the other electrode layer, a solid electrolyte layer 13 interposed between the positive electrode layer 11 and the negative electrode layer 12, a current collector 14 joined to the positive electrode layer 11, and a current collector 15 joined to the negative electrode layer 12.

[0089] The positive electrode layer 11 and the negative electrode layer 12 each have a layered shape, particularly a sheet shape, and contain an electrode active material, and the solid electrolyte layer 13 has a layered shape, particularly a sheet shape, and contains a solid electrolyte.

[0090] The solid-state battery binder may be contained in any part of the solid-state battery 10. Examples of parts in the solid-state battery 10 that contain the solid-state battery binder include the positive electrode layer 11, the negative electrode layer 12, the solid electrolyte layer 13, the interface between the positive electrode layer 11 and the solid electrolyte layer 13, and the interface between the negative electrode layer 12 and the solid electrolyte layer 13. However, it is preferable that the solid-state battery binder bonds the electrode active material constituting the electrode layer to a current collector adjacent to the electrode layer.

[0091] In other words, the binder for solid state batteries is preferably one that bonds the electrode active material (positive electrode active material) contained in the positive electrode layer 11 to the current collector 14, or one that bonds the electrode active material (negative electrode active material) contained in the negative electrode layer 12 to the current collector 15.

[0092] This makes it possible to improve the adhesion between the electrode layer and the current collector in the solid-state battery 10, and to improve the reliability of the solid-state battery 10 as a whole in a more stable manner for a longer period of time. In addition, the binder for a solid-state battery of the present invention itself exhibits excellent ion conductivity, and therefore, the solid-state battery 10 can achieve excellent charge / discharge characteristics.

[0093] In particular, it is preferable that at least one of the electrode layers, the positive electrode layer 11 and the negative electrode layer 12, contains the binder for a solid battery of the present invention.

[0094] As a result, for example, when the electrode active materials (positive electrode active material, negative electrode active material) constituting the electrode layers (positive electrode layer 11, negative electrode layer 12) are particulate, the adhesion between the electrode layers and the adjacent current collectors can be improved, and the adhesion between the electrode active materials constituting the electrode layers can also be improved, so that the reliability of the solid-state battery 10 as a whole can be improved and more stable for a longer period of time. Also, the charge and discharge characteristics of the solid-state battery 10 can be improved.

[0095] The above-mentioned effects are more pronounced when both the positive electrode layer 11 and the negative electrode layer 12 contain the binder for a solid battery of the present invention.

[0096] In the following description, a case in which both the positive electrode layer 11 and the negative electrode layer 12 contain the binder for a solid battery of the present invention will be representatively described.

[0097] [2-1] Positive electrode layer The positive electrode layer 11 contains at least a positive electrode active material.

[0098] The electrode active material contained in the positive electrode layer 11, i.e., the positive electrode active material, is usually an inorganic material. More specifically, the positive electrode active material is, for example, LiCoO2, LiNiO2, LiMn2O4, Li2Mn2O3, LiCr 0.5 Mn 0.5 Examples of the positive electrode active material include fluorides such as LiFeF3, LiBH4, Li4BN3H, and the like. 10boron complex compounds such as boron fluoride complexes, iodine complex compounds such as polyvinylpyridine-iodine complexes, and nonmetallic compounds such as sulfur can also be used.

[0099] The positive electrode layer 11 may further contain a binder for a solid battery and a solid electrolyte. When the positive electrode layer 11 contains a binder for a solid battery, the binder for a solid battery may be the same as the binder for a solid battery of the present invention described above.

[0100] When the positive electrode layer 11 contains a solid electrolyte, the solid electrolyte may be the same as the solid electrolyte contained in the solid electrolyte layer 13 described later.

[0101] When the positive electrode layer 11 contains the binder for a solid battery of the present invention, the content of the binder for a solid battery of the present invention in the positive electrode layer 11 is preferably 0.5 mass % or more and 50.0 mass % or less, more preferably 1.0 mass % or more and 40.0 mass % or less, and further preferably 1.5 mass % or more and 30.0 mass % or less.

[0102] This makes it possible to make the above-mentioned effects of the present invention even more remarkable.

[0103] [2-2] Negative electrode layer The negative electrode layer 12 contains at least a negative electrode active material.

[0104] The electrode active material contained in the negative electrode layer 12, i.e., the negative electrode active material, is usually an inorganic material. More specifically, examples of the negative electrode active material include Nb2O5, V2O5, TiO2, In2O3, ZnO, SnO2, NiO, ITO, AZO, GZO, ATO, FTO, and Li4Ti5O 12 Examples of the negative electrode active material include metals and alloys such as Li, Al, Si, Si-Mn, Si-Co, Si-Ni, Sn, Zn, Sb, Bi, In, and Au, carbon materials such as graphite and hard carbon, LiC 24Alternatively, a material in which lithium ions are inserted between layers of a carbon material such as LiC6 may be used.

[0105] The negative electrode layer 12 may further contain a binder for a solid battery and a solid electrolyte. When the negative electrode layer 12 contains a binder for a solid battery, the binder for a solid battery may be the same as the binder for a solid battery of the present invention described above.

[0106] When the negative electrode layer 12 contains a solid electrolyte, the solid electrolyte may be the same as the solid electrolyte contained in the solid electrolyte layer 13 described later.

[0107] When the negative electrode layer 12 contains the binder for a solid battery of the present invention, the content of the binder for a solid battery of the present invention in the negative electrode layer 12 is preferably 0.5 mass % or more and 40.0 mass % or less, more preferably 1.0 mass % or more and 30.0 mass % or less, and even more preferably 1.5 mass % or more and 20.0 mass % or less. This makes it possible to make the above-mentioned effects of the present invention even more remarkable.

[0108] [2-3]Solid electrolyte layer The solid electrolyte layer 13 is configured to include a solid electrolyte.

[0109] [2-3-1] Solid electrolyte The solid electrolyte constituting the solid electrolyte layer 13 contains a resin material for a solid electrolyte and a lithium salt.

[0110] When the resin material constituting the solid electrolyte has a lithium salt structure in its molecule, the solid electrolyte contains a lithium salt other than the resin material.

[0111] Examples of the resin material for the solid electrolyte include (meth)acrylic ester-based polymers, (meth)acrylamide-based polymers, polyvinylidene fluoride, and polymers synthesized using salt monomers composed of an onium cation having a polymerizable functional group and an organic anion having a polymerizable functional group.

[0112] Among the above polymers, a polymer synthesized using a salt monomer composed of an onium cation having a polymerizable functional group and an organic anion having a polymerizable functional group is preferred, as this allows for better charge / discharge characteristics to be obtained.

[0113] Examples of the (meth)acrylic ester-based polymer and (meth)acrylamide-based polymer in the polymer include polymers synthesized using monomers such as N,N-dimethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, methyl (meth)acrylate, stearyl acrylate, diacetone acrylamide, 1-adamantyl (meth)acrylate, and 2-ethyladamantyl (meth)acrylate.

[0114] The salt monomer is composed of an onium cation having a polymerizable functional group and an organic anion having a polymerizable functional group. The onium cation having a polymerizable functional group is a fluoronium cation (F + ), oxonium cation (O + ), sulfonium cation (S + ), ammonium cation (N + ) and phosphonium cations (P + In particular, from the viewpoints of versatility and workability, phosphonium cations, sulfonium cations and ammonium cations are more preferred, and among these, ammonium cations are the most preferred.

[0115] As the resin material for the solid electrolyte, for example, a polyethylene oxide compound can be used.

[0116] In this specification, the polyethylene oxide compound refers to polyethylene oxide and a compound in which at least one hydroxyl group of polyethylene oxide is etherified with an alkyl group having 1 to 6 carbon atoms.

[0117] That is, in this specification, the polyethylene oxide compound refers to a compound represented by the following formula [V].

[0118] R 5 O(CH2CH2O) m R 6 [V] (In formula [V], R 5 and R 6 are each independently a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, and m is an integer of 2 or more.

[0119] In particular, R in the above formula [V] 5 and R 6 is preferably a hydrogen atom or a methyl group.

[0120] The weight average molecular weight of the polyethylene oxide compound is preferably 500 or more and 100,000 or less, more preferably 1,000 or more and 80,000 or less, and even more preferably 2,000 or more and 50,000 or less.

[0121] The resin material for a solid electrolyte may contain, for example, the binder for a solid battery of the present invention. That is, the resin material for a solid electrolyte may contain a resin component having a norbornene-derived structure in the main chain and an ethylene oxide structure in the side chain.

[0122] However, when the binder for solid batteries of the present invention is contained as a constituent component of a resin material for solid electrolytes, the weight average molecular weight of the constituent component is preferably 10,000 or more and 400,000 or less, more preferably 30,000 or more and 350,000 or less, and even more preferably 50,000 or more and 300,000 or less.

[0123] This makes it possible to achieve a higher level of compatibility between the ionic conductivity of the solid electrolyte resin material and the stability and ease of handling of the sheet when processed into a sheet material as described below.

[0124] When the binder for a solid battery of the present invention is contained as a resin material for a solid electrolyte, the average degree of polymerization of the constituent components is preferably 10 or more and 1,350 or less, more preferably 20 or more and 1,130 or less, and even more preferably 30 or more and 900 or less.

[0125] This makes it possible to achieve a higher level of compatibility between the ionic conductivity of the solid electrolyte resin material and the stability and ease of handling of the sheet when processed into a sheet material as described below.

[0126] When the binder for a solid battery of the present invention is contained as a resin material for a solid electrolyte, the softening point of the constituent components is preferably −30° C. or higher and 150° C. or lower, more preferably −20° C. or higher and 135° C. or lower, and even more preferably −15° C. or higher and 120° C. or lower.

[0127] This makes it possible to achieve a higher level of compatibility between the ionic conductivity of the solid electrolyte resin material and the stability and ease of handling of the sheet when processed into a sheet material as described below.

[0128] The content of the resin material for the solid electrolyte in the solid electrolyte is not particularly limited, but the ratio to the total solid content of the solid electrolyte is preferably 45.0 mass % or more and 90.0 mass % or less, more preferably 50.0 mass % or more and 88.0 mass % or less, and even more preferably 55.0 mass % or more and 85.0 mass % or less. This makes it possible to improve the ionic conductivity of the solid electrolyte.

[0129] The lithium salt contained in the solid electrolyte is not particularly limited, but is preferably at least one selected from the group consisting of LiSCN, LiN(CN)2, LiClO4, LiBF4, LiAsF6, LiPF6, LiCF3SO3, Li(CF3SO2)2N, Li(CF3SO2)3C, LiSbF6, Li(FSO2)2N, LiC4F9SO3, LiN(SO2CF2CF3)2, LiPF3(CF2CF3)3, LiPF3(C2F5)3, LiPF3(CF3)3, LiCl, LiF, LiBr, LiI, LiB(C2O4)2, lithium difluoro(oxalate)borate, and lithium bis(oxalate)borate, and is more preferably Li(CF3SO2)2N. This makes it possible to improve the ionic conductivity of the solid electrolyte.

[0130] The content of the lithium salt in the solid electrolyte is not particularly limited, but the ratio to the total solid content of the solid electrolyte is preferably 5.0 mass % or more and 55.0 mass % or less, more preferably 10.0 mass % or more and 50.0 mass % or less, and even more preferably 15.0 mass % or more and 45.0 mass % or less. This makes it possible to improve the ionic conductivity of the solid electrolyte.

[0131] The solid electrolyte may further include, for example, an inorganic solid electrolyte. Examples of inorganic solid electrolytes include LiLaZrO-based compounds, LiLaZrNbO-based compounds, LiLaZrTaO-based compounds, LiLaTaO-based compounds, LiLaTiO-based compounds, LiAlGePO-based compounds, LiAlTiPO-based compounds, LiPO-based compounds, LiSiO-based compounds, LiBO-based compounds, LiPS-based compounds, and LiPSCl-based compounds.

[0132] When the solid electrolyte contains an inorganic solid electrolyte, the proportion of the inorganic solid electrolyte in the total solid content of the solid electrolyte is preferably 10.0 mass % or more and 95.0 mass % or less, more preferably 15.0 mass % or more and 90.0 mass % or less, and even more preferably 20.0 mass % or more and 85.0 mass % or less. This makes it possible to provide the solid electrolyte with superior strength and ionic conductivity.

[0133] The solid electrolyte may further contain, for example, a nonaqueous solvent used in the electrolytic solution.

[0134] Examples of non-aqueous solvents include cyclic carbonates such as ethylene carbonate (EC) and vinylene carbonate (VC), chain carbonates such as diethyl carbonate (DEC), dimethyl carbonate (DMC), and methyl ethyl carbonate (MEC), cyclic ethers such as tetrahydrofuran (THF), 2-methyl tetrahydrofuran (2MeTHF), and dioxolane (DOX), chain ethers such as dimethoxyethane (DME) and diethoxyethane (DEE), γ-butyrolactone (GBL), acetonitrile (AN), and sulfolane (SL), etc. These non-aqueous solvents can be used alone or as a mixture.

[0135] When the solid electrolyte contains a non-aqueous solvent, the proportion of the non-aqueous solvent in the total solid content of the solid electrolyte is preferably 0.1 mass % or more and 95.0 mass % or less, more preferably 1.0 mass % or more and 92.0 mass % or less, and even more preferably 3.0 mass % or more and 90.0 mass % or less.

[0136] This makes it possible to improve the ease of handling of the solid electrolyte, the ion conductivity, and the interface formation with the composite.

[0137] The solid electrolyte may further contain a liquid component that is liquid at 25°C, for example.

[0138] This improves the ease of handling of the solid electrolyte, and allows the formation of the solid electrolyte to be carried out more suitably.

[0139] Examples of the liquid component include alcohols such as methanol, ethanol, isopropanol, butanol, octanol, and benzyl alcohol; esters such as ethyl acetate, butyl acetate, ethyl lactate, γ-butyrolactone, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, methyl 3-methoxypropionate, ethyl 3-ethoxypropionate, butyl butyrate, and methyl benzoate; dioxane, 1,2-dimethoxyethane, tetrahydrofuran (THF), ethylene glycol monobutyl ether, propylene glycol monomethyl ether, ethylene diglycol monomethyl ether, ethylene diglycol ethyl ether, and the like. ethers such as dimethyl ether; amides such as N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, diisobutyl ketone (DIBK), cyclohexanone; nitriles such as acetonitrile; aromatic hydrocarbons such as benzene, toluene, xylene, trimethylbenzene (mesitylene, hemimelitene, pseudocumene), ethylbenzene, tetralin, and derivatives thereof (for example, compounds in which the hydrogen atoms of these compounds are substituted with other atoms or atomic groups (functional groups, etc.)), and the like. One or more selected from these can be used in combination.

[0140] When the solid electrolyte contains the liquid component, the proportion of the liquid component in the solid electrolyte is preferably 0.001% by mass or more and 10.0% by mass or less, and more preferably 0.005% by mass or more and 5.0% by mass or less.

[0141] This makes it possible to more suitably remove liquid components during the formation of the solid electrolyte while improving the ease of handling of the solid electrolyte, thereby improving the productivity of the solid electrolyte.

[0142] Solid electrolyte layer 13 may contain components other than the above-mentioned components. Hereinafter, such components are also referred to as "other components".

[0143] Examples of other components include adhesion aids, leveling agents, defoamers, colorants, antioxidants, flame retardants, inorganic fillers such as silica, medium-chain normal alkanes such as paraffin and petrolatum, natural materials such as rosin, pine resin, and Canada balsam, and glymes such as butyl glyme and tetraglyme.

[0144] However, the proportion of other components in solid electrolyte layer 13 is preferably 10.0 mass % or less, more preferably 5.0 mass % or less, and even more preferably 3.0 mass % or less.

[0145] [2-4] Current collector (positive electrode current collector) A current collector (positive electrode current collector) 14 is provided on the surface of the positive electrode layer 11 opposite to the surface facing the solid electrolyte layer 13.

[0146] The current collector 14 is usually made of an inorganic material as described below. When the portion in contact with the current collector 14 and the positive electrode layer 11 made of such an inorganic material is made of a material containing the binder for a solid battery of the present invention, the adhesion between the positive electrode layer 11 and the current collector 14 can be improved, and the reliability of the solid battery 10 can be improved.

[0147] The current collector 14 is a conductor provided to transfer electrons to and from the positive electrode layer 11. The current collector 14 is usually made of a material that has a sufficiently low electrical resistance and whose electrical conduction characteristics and mechanical structure do not change substantially due to charging and discharging. Specifically, for example, Al, Ti, Pt, Au, Cu, Ni, etc. are preferably used, and alloy materials such as stainless steel are also preferably used depending on the application. Among them, Al is particularly preferably used for the positive electrode current collector 14.

[0148] The shape of the current collector 14 is not particularly limited, and examples thereof include a foil shape, a plate shape, and a mesh shape.

[0149] [2-5] Current collector (negative electrode current collector) A current collector (negative electrode current collector) 15 is provided on the surface of the negative electrode layer 12 opposite to the surface facing the solid electrolyte layer 13.

[0150] The current collector 15 is usually made of an inorganic material as described below. When the portion in contact with the current collector 15 and the negative electrode layer 12 made of such an inorganic material is made of a material containing the binder for a solid battery of the present invention, the adhesion between the negative electrode layer 12 and the current collector 15 can be improved, and the reliability of the solid battery 10 can be improved.

[0151] The current collector 15 is a conductor provided to transfer electrons to and from the negative electrode layer 12. Specifically, for example, Al, Ti, Pt, Au, Cu, Ni, etc. are preferably used as the current collector 15, and alloy materials such as stainless steel are also preferably used depending on the application. Among them, Cu and Ni are particularly preferably used for the current collector 15 of the negative electrode.

[0152] The shape of the current collector 15 is not particularly limited, and examples thereof include a foil shape, a plate shape, and a mesh shape.

[0153] [2-6] Battery applications The solid-state battery 10 may be used for any purpose. Examples of electronic devices to which the solid-state battery 10 is applied as a power source include mobile phones, smartphones, tablet terminals, video cameras, calculators, electronic game devices, personal computers, digital cameras, and the like. The solid-state battery 10 may also be applied to, for example, moving objects such as automobiles. More specifically, the solid-state battery 10 can be suitably applied to, for example, storage batteries for electric vehicles, plug-in hybrid vehicles, hybrid vehicles, fuel cell vehicles, and the like. The solid-state battery 10 can also be applied to, for example, household power sources, industrial power sources, solar power storage batteries, and the like.

[0154] [3] Sheet material In the battery of this embodiment, at least one of the positive electrode layer 11, the negative electrode layer 12, and the solid electrolyte layer 13 may be formed using a sheet material.

[0155] The thickness of the sheet material is not particularly limited, but is preferably 5 μm or more and 5000 μm or less, and more preferably 10 μm or more and 1000 μm or less.

[0156] This makes it easier for the sheet material itself to maintain its mechanical strength in a more suitable manner, making it easier to handle the sheet material during the battery manufacturing process and the like.

[0157] The sheet material may be produced by any method, but can be suitably produced by, for example, the following method.

[0158] That is, a composition containing the constituent material of the positive electrode layer 11, the negative electrode layer 12, or the solid electrolyte layer 13, or a precursor thereof, is formed into a sheet, thereby obtaining a sheet material.

[0159] Examples of the precursor of the constituent material of the sheet material that can be contained in the composition include oligomers and prepolymers that correspond to the resin components that constitute the binder for solid state batteries of the present invention described above.

[0160] When a composition containing a liquid component is used to manufacture a sheet material, for example, an excess amount of the liquid component may be used when preparing the composition, and a portion of the liquid component may be removed before forming the composition into a sheet to form a slurry.

[0161] When a sheet material is produced using a composition containing a liquid component, for example, a layer is formed using various coating methods such as cast coating, and then the liquid component is removed from the layer, thereby making it possible to obtain a suitable sheet material.

[0162] In addition, a part of the liquid component used in the manufacturing process may remain in the sheet material, and in such a case, the liquid component may be removed during the manufacturing process of the battery.

[0163] Although a preferred embodiment of the present invention has been described above, the present invention is not limited to the above, and modifications and improvements within the scope of the present invention that can achieve the object of the present invention are included in the present invention.

[0164] For example, the present invention is not limited to being applied to the above-mentioned solid-state battery. More specifically, for example, the battery of the present invention may be a battery other than a solid-state battery, such as a fuel cell or a redox flow battery. EXAMPLES

[0165] The present invention will be described in detail below based on examples, but the present invention is not limited thereto.

[0166] [4] Preparation of binder for solid-state batteries Example 1 First, 91.37 g (404.00 mmol) of the compound represented by the following formula [III] was dissolved in a mixed solvent of 228.86 g of toluene and 276.51 g of ethyl acetate, and the solution was filled into a reaction vessel.

[0167] [ka]

[0168] The solution was sparged with nitrogen for 30 minutes to remove oxygen and then heated to 50° C. Once the solution reached 50° C., a solution of 0.784 g (1.62 mmol) of (η6-toluene)Ni(C6F5)2 in 258.43 g of toluene (prepared in the glove box) was added to the reaction vessel via syringe. The mixture was stirred at 50° C. for 3.0 hours, after which 0.73 g (40.40 mmol) of a 30 wt % aqueous solution of H2O2 was added.

[0169] Next, the above reaction mixture was treated with 21.24 g (353.7 mmol) of acetic acid and 41.38 g (1216.5 mmol) of 30 wt % H2O2 aqueous solution to remove Ni residues, and then washed with water and isopropyl alcohol (IPA).

[0170] The solvent was then removed by evaporation using a rotary evaporator to obtain a polymerization reaction product. The polymerization reaction product was dissolved in the same mass of acetone, and then added to a 14-fold excess amount of heptane and stirred to remove unreacted monomers.

[0171] The product obtained in the above step was dried in a vacuum at 60° C. for 16 hours to isolate 59 g (yield: 60%) of a resin component as a binder for solid-state batteries represented by the following formula [IV].

[0172] [ka]

[0173] The resin component obtained as described above had a weight average molecular weight of 157,000, an average degree of polymerization of 370, and a softening point of 105°C.

[0174] (Examples 2, 3, 4, and 5) The resin components were produced and isolated in the same manner as in Example 1, except that the reaction conditions were changed so that the weight average molecular weight and softening point conditions were as shown in Table 1.

[0175] Comparative Example 1 In this comparative example, a commercially available PVDF (polyvinylidene fluoride), KF Polymer #1100 manufactured by Kureha Corporation, was prepared as a resin component for a binder for solid-state batteries.

[0176] Table 1 shows the conditions (weight average molecular weight, softening point) of the binder for solid state batteries in each of the above examples.

[0177] [Table 1]

[0178] [5] Preparation of test samples [5-1] Creating a sample using copper foil FIG. 2 is a diagram illustrating a method for producing a test sample in this example.

[0179] First, the binder for solid-state batteries of Example 1 was dissolved in toluene to prepare a varnish (FIG. 2(a)). The resin content in the varnish was 30 to 70 mass %.

[0180] The obtained varnish was applied to a specified thickness on a copper foil having a thickness of 15 μm using a doctor blade, and then dried. The copper foil used was electrolytic copper foil (NC-WS) manufactured by Furukawa Electric Co., Ltd. (Figures 2(b) and (c)).

[0181] Copper foil was placed on top of the varnish applied to the copper foil to form a laminate, and the laminate was then melt-pressed by vacuum pressing (Figure 2(d)).

[0182] The laminate was diced to a specified size (Figure 2(e)). To prevent the copper foil from tearing, a test sample was prepared by reinforcing the copper foil with Kapton tape (Figure 2(f)).

[0183] Instead of the binder for solid batteries of Example 1, the binders for solid batteries of Examples 2, 3, 4, and 5 and Comparative Example 1 were used to manufacture test samples.

[0184] In addition, since the binder for solid-state batteries (PVDF) of Comparative Example 1 has low solubility in solvents, for Comparative Example 1, the binder was not made into a varnish but was applied in powder form directly onto the copper foil. Except for this, a test sample was prepared in the same manner as described above.

[0185] [5-2] Creating a sample using aluminum foil Test samples were prepared in the same manner as described in [5-1] above, except that aluminum foil was used instead of copper foil.

[0186] [5-3] Creating a sample using nickel foil Test samples were prepared in the same manner as described in [5-1] above, except that nickel foil was used instead of copper foil.

[0187] [6] Evaluation [6-1] Adhesion Using each test sample prepared in [5] above, a peel test was carried out as described below to evaluate the adhesion.

[0188] FIG. 3 is a photograph illustrating the method of the peel test in this example. As shown in FIG. 3, the ends of the upper and lower Kapton tapes of the test sample were clamped and pulled upward and downward (pseudo 180° peel) to peel them off.

[0189] The peel strength when the metal foil and the binder for a solid battery were peeled off was evaluated as the adhesion strength between the metal foil and the binder for a solid battery.

[0190] The results of the adhesion between the copper foil and the binder for solid-state batteries are shown in Table 2, the results of the adhesion between the aluminum foil and the binder for solid-state batteries are shown in Table 3, and the results of the adhesion between the nickel foil and the binder for solid-state batteries are shown in Table 4.

[0191] [Table 2]

[0192] [Table 3]

[0193] [Table 4]

[0194] As is clear from Tables 2 to 4, it was found that the binder for solid state batteries of the present invention has high adhesion to all of copper foil, aluminum foil, and nickel foil.

[0195] Although the results of Example 2 are not shown in Tables 2 to 4, good results were obtained for Example 2 as well as for Examples 1 and 3.

[0196] In contrast, the PVDF of the comparative example did not provide sufficient adhesion to the copper foil, aluminum foil, and nickel foil. In particular, the binder for solid-state batteries (PVDF) attached to the nickel foil of the comparative example peeled off spontaneously.

[0197] In addition, instead of using metal foil, the adhesion to the positive electrode active material and the negative electrode active material was evaluated. As described above, excellent results were obtained in each of the examples, whereas satisfactory results were not obtained in the comparative examples.

[0198] From the above, it is considered that by using the binder for a solid battery of the present invention, it is possible to achieve excellent adhesion to the electrode active material and the current collector.

[0199] [6-2] Tensile strength For each of the solid-state battery binders of the Examples and Comparative Examples, a tensile strength test was carried out in accordance with JIS-K7127 (1999) to obtain a stress-strain curve.

[0200] The stress-strain curves for the binders for solid batteries of Examples 1 and 3 are shown in FIG. 4, and the stress-strain curve for the binder for solid batteries of Comparative Example 1 is shown in FIG.

[0201] 4, the breaking elongation was more than about 80% for both the binders for solid state batteries in Examples 1 and 3. The yield point elongation was about 11% for both Examples 1 and 3, and the tensile yield stress was about 4 N / mm for Example 1 and about 4.8 N / mm for Example 3. It is estimated that the binder for solid state batteries is plastically deformed in the region from the yield point to the breaking point.

[0202] In contrast, as shown in FIG. 5, the binder for a solid battery in Comparative Example 1 had a breaking elongation of 7% and a tensile breaking stress of about 39 N / 10 mm.

[0203] From these results, it is understood that the binders for solid state batteries of Examples 1 and 3 have superior elongation properties compared to Comparative Example 1. Note that, for Examples 2, 4, and 5, similarly to Examples 1 and 3, good results were obtained.

[0204] [6-3] Solvent solubility The binder for a solid battery of Example 1 was used to evaluate the solvent solubility as follows.

[0205] That is, 0.1 g of the binder for solid batteries of Example 1 was dissolved in 1 mL of each of the solvents No. 1 to No. 15 shown in Table 5, and the solution was stirred for 3 hours using a mix rotor variable manufactured by AS ONE Corporation. The state of the solution after stirring was visually observed, and the solubility in each solvent was evaluated according to the following criteria.

[0206] 1: Insoluble 2: Slightly melts (obviously becomes softer) 3: Somewhat soluble, liquid becomes very cloudy 4: Dissolves, but the liquid becomes slightly cloudy 5: Dissolved, the liquid became clear The results are shown in Table 5.

[0207] [Table 5]

[0208] As is clear from Table 5, it was found that the binder for solid batteries of Example 1 has high solubility in a wide variety of solvents including low polarity solvents. In addition, in Examples 2 to 5, as in Example 1, good results were obtained.

[0209] In addition, test samples were prepared in the same manner as in the above-mentioned Examples, except that the weight average molecular weight of the binder for solid batteries was changed within a range of 10,000 to 400,000, the average polymerization degree of the binder for solid batteries was changed within a range of 25 to 1800, and the softening point of the binder for solid batteries was changed within a range of 25°C to 120°C. The test samples were then evaluated in the same manner as in the above-mentioned Examples, and excellent results were obtained as in the above-mentioned Examples. [Explanation of symbols]

[0210] 10: Solid state battery 11: Positive electrode layer 12: Negative electrode layer 13: Solid electrolyte layer 14: Current collector (positive electrode current collector) 15: Current collector (negative electrode current collector)

Claims

1. A binder for solid-state batteries, comprising a resin component having a norbornene-derived structure in its main chain and an ethylene oxide structure in its side chain.

2. The binder for a solid battery according to claim 1 , wherein the resin component contains a monomer component represented by the following formula (NB): 【Chemistry 1】 (In formula (NB), R 1 is a hydrogen atom or a hydrocarbon group, R 2 , R 3 and R 4 are each independently a hydrogen atom or an organic group having 1 to 3 carbon atoms, n is an integer of 1 or more, 1 is 0, 1 or 2.)

3. The binder for a solid battery according to claim 2, wherein n in the formula (NB) is an integer of 2 or more and 6 or less.

4. The binder for a solid battery according to claim 2 or 3, wherein the monomer component is represented by the following formula [I]: 【Chemistry 2】 (In formula [I], n is an integer of 1 or more, and R is a hydrogen atom or a hydrocarbon group.)

5. 4. The binder for a solid battery according to claim 1, wherein the resin component has a weight average molecular weight of 10,000 or more and 400,000 or less.

6. 4. The binder for a solid battery according to claim 1, wherein the average degree of polymerization of the resin component is 25 or more and 1,800 or less.

7. 4. The binder for a solid battery according to claim 1, wherein the softening point of the resin component is 25° C. or higher and 120° C. or lower.

8. 4. The binder for a solid battery according to claim 1, which bonds an electrode active material contained in a positive electrode layer to a current collector.

9. 4. The binder for a solid battery according to claim 1, which bonds an electrode active material contained in a negative electrode layer to a current collector.

10. A positive electrode layer; A negative electrode layer; an electrolyte layer located between the positive electrode layer and the negative electrode layer; A solid-state battery comprising: A solid-state battery comprising the binder for a solid-state battery according to claim 1 .

Citation Information

Patent Citations

  • Vinylidene fluoride polymer powder, binder composition, electrode mixture, and method for manufacturing electrode

    JP7044673B2

Cited By

  • Binder for electrode of secondary battery

    WO2026191329A1